Demystifying service quality of Multimodal Transportation Hub (MMTH) through measuring users' satisfaction of public transport. (March 2021) - Chauhan, Vivek; Gupta, Akshay; Parida, Manoranjan
Abstract: The present study attempts to explore the factors and their effects which influence the service quality of Multimodal Transportation Hub (MMTH) in Anand Vihar, Delhi. Total 515 samples are collected using satisfaction survey of public transport users. Exploratory factor analysis provides the six-factor solution and the same is confirmed using the confirmatory factor analysis. These factors are 'transfer environment & important facilities', 'safety & security', 'transport modes and travel information', 'accessibility & signposting', 'comfort, convenience & quality of environment' and 'staff management & ticketing'. Structural Equation Modelling is used to identify relationships between service quality attributes and overall service quality. Results of the study show that service quality of MMTH is mostly affected by the transfer environment & important facilities (γ = 0.36) followed by safety & security (γ = 0.33). The results also demonstrate that evaluation of the overall service quality is better explained when people give ratings after knowing about the various attributes of the MMTH's service quality. An external validation test is carried out, and results suggest that the values of service quality lie within the mean error range of ±6.5%, which presents the richness of the model. The findings of the study will help the government, operators and transport planners to formulate the policies in order to improve the service quality of the multimodal hub and ultimately promote the use of public transport. Highlights: This paper explores the factors influencing the service quality of Multimodal Transportation Hub (MMTH). The Study deploys SEM to identify relationships among various attributes and overall service quality. Six latent factors are found affecting the overall service quality of MMTH. MMTH's service quality is mostly affected by transfer environment & important facilities followed by safety & security.